VALIDITY OF PLANT TISSUE ATLAS FOR SENIOR HIGH SCHOOL - Yudi Agustira Rahmatullah; Helendra Helendra; Ganda Hijrah Selaras; Ardi Ardi (Universitas Negeri Padang, 2021)
Biological learning requires students to carry out observations in practical activities as a form of understanding concepts. Based on observations of researchers in class XI of SMAN 3 and SMAN 7 Padang, it was found that the school had carried out practical activities well on biology learning, but students had difficulty in practicing plant tissue. Students do not find clear observations, students are less skilled in using microscopes and making plant preparations, some microscopes have moldy lenses, and the availability of valid practicum media is not available and contains photos of observations of plant tissue, so observing plant tissues what was done did not run smoothly. This research is a development research. The research subjects were 28 students, one teacher, and three lecturers. The instruments used in this study were interview guides and validity questionnaires. Based on the research conducted, products have been produced in the form of Atlas of Plant Networks for SMA / MA. Validity test results with an average value of 3.73. with very valid criteria in terms of the feasibility of content, language and readability, and presentation. So that the Atlas of the Body Network can be said to be a valid media.